Edu Parenting sebagai Sarana Sosialisasi Pengetahuan dan Pemahaman Orang Tua Terhadap Gizi Seimbang Anak Usia Dini - Erina Erina; Diana Dwi Jayanti; Dina Fitriana; Imas Jihansyah (JCE (Journal of Childhood Education), 2023)
This study entitled "Edu-parenting as a means of disseminating knowledge and understanding of parents on balanced nutrition for early childhood at SPS Roudlotul Jannah". This was motivated by the knowledge and understanding of parents regarding balanced nutrition for early childhood which has an important role for children because it will affect their growth and development. As an educational institution which was also a place for children to grow and develop, the school should also anticipate this by organizing an educational parenting activity as a means of disseminating knowledge and understanding of balanced nutrition for early childhood, so that parents can provide optimal and appropriate balanced nutrition consumption patterns for their children. Based on preliminary study conducted by researchers, it was known that the average parents at SPS Roudlotul Jannah, who was the participant in this research, still didn’t have optimal knowledge and understanding of balanced nutrition according to the needs of the child's body. This study used a descriptive qualitative approach and is a type of field research with 10 subjects. The results of this study indicated that the edu parenting activities carried out on April 4, 2023 can be used as a means of socializing parental knowledge and understanding of balanced nutrition for early childhood which can be seen from the inscreasing of : (1) new knowledge and understanding of balanced nutrition for early childhood, and (2) the commitment and awareness of parents regarding the provision of balanced nutrition for children after participating in edu-parenting activities.